Phthalate and gallstones: the mediation of insulin - Tang, Haoxian; Zhang, Xuan; Huang, Jingtao; Luo, Nan; Chen, Hongyu; Yang, Qinglong; Lin, Hanyuan; Hua, Hao (Frontiers in Public Health, 2024)
Background Exposure to a mixture of environmental chemicals may cause gallstone, but the evidence remains equivocal. The current study aims to investigate the association between phthalate metabolites and gallstones, and to explore their mediators. Methods Data from the National Health and Nutrition Examination Survey 2017–2018 on U.S. adults (≥20 years) were analyzed to explore the association between phthalate metabolites and gallstones by employed survey-weighted logistic regression, restricted cubic spline (RCS), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR). Mediation analyses examined the role of oxidative stress markers, inflammatory markers, metabolic syndrome, body composition, diabetes, and insulin. Results The current study included 1,384 participants, representing 200.6 million U.S. adults. Our results indicated a significant association between phthalate metabolites, particularly high molecular weight metabolites such as Di(2-ethylhexyl) phthalate (DEHP) and 1,2-Cyclohexane dicarboxylic acid diisononyl ester (DINCH), and gallstones. Furthermore, mediation analyses indicated that phthalate metabolites may play a role in the development of gallstones by influencing insulin secretion. Subgroup analyses did not reveal significant interaction. Conclusion The association between exposure to phthalates and the occurrence of gallstones, potentially mediated by hyperinsulinemia from a nationally representative epidemiological perspective. These insights contribute to a better understanding of the potential health implications of plasticizers, emphasizing the need for proactive management measures.